Enhanced Precision in the Convergent Procedure for Persistent Atrial Fibrillation Using Real‐Time Intraoperative 3D Electrophysiological Mapping - Ujjawal Kumar; Usman Aslam; Leslie Epting; Anthony Cooper; Alyssa Abraham; Zain Khalpey (Clinical Case Reports)
ABSTRACT Real‐time intraoperative electrophysiological mapping significantly enhances the precision and efficiency of ablations in epicardial ablation (Convergent procedure) for persistent atrial fibrillation. This novel approach improves patient outcomes by enabling targeted ablation of affected tissues, reducing unnecessary burns, and ensuring discharge in sinus rhythm, as we demonstrate.